Single shot quantitative polarized light imaging system for rapid planar biaxial testing of soft tissues - Blair, Michael J.; Quinn, Kyle P. (Frontiers in Bioengineering and Biotechnology, 2022)
Quantitative Polarized Light Imaging (QPLI) is an established technique used to compute the orientation of collagen fibers based on their birefringence. QPLI systems typically require rotating linear polarizers to obtain sufficient data to estimate orientation, which limits acquisition speeds and is not ideal for its application to mechanical testing. In this paper, we present a QPLI system designed with no moving parts; a single shot technique which is ideal to characterize collagen fiber orientation and kinematics during mechanical testing. Our single shot QPLI system (ssQPLI) sorts polarized light into four linear polarization states that are collected simultaneously by four cameras. The ssQPLI system was validated using samples with known orientation and retardation, and we demonstrate its use with planar biaxial testing of mouse skin. The ssQPLI system was accurate with a mean orientation error of 1.35° ± 1.58°. Skin samples were tested with multiple loading protocols and in each case the mean orientation of the collagen network reoriented to align in the direction of primary loading as expected. In summary, the ssQPLI system is effective at quantifying collagen fiber organization, and, when combined with mechanical testing, can rapidly provide pixel-wise measures of fiber orientation during biaxial loading.